2021
DOI: 10.1021/acsnano.1c01755
|View full text |Cite
|
Sign up to set email alerts
|

Phytoglycogen Nanoparticles: Nature-Derived Superlubricants

Abstract: Phytoglycogen nanoparticles (PhG NPs), a single-molecule highly branched polysaccharide, exhibit excellent water retention, due to the abundance of close-packed hydroxyl groups forming hydrogen bonds with water. Here we report lubrication properties of close-packed adsorbed monolayers of PhG NPs acting as boundary lubricants. Using direct surface force measurements, we show that the hydrated nature of the NP layer results in its striking lubrication performance, with two distinct confinement-controlled frictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…The combination of the therapeutic effect and lubrication may provide synergy for the treatment of shearinduced arthritis. Together with excellent lubrication properties of PhG NPs, which were demonstrated in our earlier work, 20 the results reported in the present study stimulate further exploration of biomedical applications of nanoconjugates of PhG NPs, with a potential effect of the endogenous albumin in synovial fluids on the release of MTX considered for in vivo studies. Intra-articular injection of PhG NP-BSA-MTX nanoconjugates may provide an alternative treatment for osteoarthritis due to their lubricating properties and the stimuli-responsive release of the antiarthritic drug.…”
Section: ■ Conclusionsupporting
confidence: 84%
See 2 more Smart Citations
“…The combination of the therapeutic effect and lubrication may provide synergy for the treatment of shearinduced arthritis. Together with excellent lubrication properties of PhG NPs, which were demonstrated in our earlier work, 20 the results reported in the present study stimulate further exploration of biomedical applications of nanoconjugates of PhG NPs, with a potential effect of the endogenous albumin in synovial fluids on the release of MTX considered for in vivo studies. Intra-articular injection of PhG NP-BSA-MTX nanoconjugates may provide an alternative treatment for osteoarthritis due to their lubricating properties and the stimuli-responsive release of the antiarthritic drug.…”
Section: ■ Conclusionsupporting
confidence: 84%
“…The hyperbranched nature and high density of hydroxyl groups of PhG NPs facilitate their hydrogen bonding with water and result in strong water retention and orientation and ordering of water molecules within the NPs . Importantly, recently, our group has shown that highly hydrated PhG NPs confined between two solid surfaces exhibit excellent lubrication properties …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These (PEI-SA/DNA) HA particles exhibited a uniform distribution with an average diameter of 179 nm (Figures 2B-D). While these particles appeared smaller in TEM images, this is likely attributable to the drying of these samples during the sample preparation procedure, given that the presence of a layer that is hydrated in aqueous solutions results in larger apparent particle sizes upon DLS-based analysis (Adibnia et al, 2021).…”
Section: Accession Numbermentioning
confidence: 99%
“…14,15 These properties imbue PG with a globular shape, with a hydrodynamic diameter between 20 and 25 nm, 13,16,17 which, together with its soft colloidal character, have motivated recent studies to employ it as an optical probe, 18 a drug delivery vehicle, 19,20 a solubilizer, 21−24 and a lubricant. 25 Although glycogen and PG have been the subject of smallangle neutron scattering (SANS) and small-angle X-ray scattering (SAXS) studies that have elucidated its properties in water, 26−28 PG aggregation behavior in poor solvent conditions has not been investigated with small-angle scattering techniques. Although the stability of PG in water is influenced by its branching degree 29 and one can precipitate PG with high-volume-percentage ethanol 30,31 or a surfactant such as sodium dodecyl sulfate, 32 the characteristics of PG at low and moderate ethanol concentrations are still poorly understood.…”
Section: ■ Introductionmentioning
confidence: 99%